Interactivity as a metaphor of online news - Fortunati, Leopoldina (Javnost (Ljubljana), 2010)
Have users challenged the power of incumbent media through interactivity, and,if so, to what extent and to what end? The front pages and their linked features of online newspapers in Bulgaria, Estonia, Ireland and Italy are examined as instances of interactivity in practice. A methodological path to analyse interactivity practices in online newspapers is proposed. The structures and the more frequent models of interactivity applied; the types of forums; the communicative flux between readers and editorial staffs; modalities of self-presentation, both of readers and journalists; and the rituality of their relations in forums are set out and analysed from a number of perspectives. The study demonstrates that online newspapers in the first stage of internet diffusion remain in a stage of pre-interactivity.
Keywords: mass media; množični mediji; elektronski časopisi; množično komuniciranje; forumi